Self-reported vision health status among older people in the Kassena-Nankana District, Ghana - Henrietta Akuamoah-Boateng (Global Health Action, 2013)
Background: If current trends continue, Ghana's aged population will increase in the coming decades. Currently, there is little knowledge on the health of the aged in Ghana. Research on vision problems among this group is virtually non-existent. This research gap needs to be filled immediately in order to promote the general health among older people in Ghana. Objective: The objective of the study was to analyse vision health and its determinants among the older adult population in a district in one of the poorest regions in Ghana – the Kassena-Nankana district. Methods: Data were obtained from the WHO multi-country studies unit (SAGE). A total of 4,294 people over the age of 50 responded to the survey. Data analysis was conducted using Stata statistical package. The aim of the analysis was to identify the prevalence of self-reported vision problems and assistive device use. Age, level of education, marital status, living arrangement, socio-economic status and proportion of people aged 50 and over in a household were used as determinants of vision health. Results: In total, 54 and 63% (p-value, 0.00) of men and women reported having far-sightedness, while 35% of men and 40.6% of women reported having near-sightedness (p-value, 0.00). In total, 33.5% of men and 38.6% of women reported having both near-sightedness and far-sightedness (p-value, 0.00). Of those who reported having either vision problems, 2.9% reported the use of visual assistive devices. Men had a higher assistive device use of 4.5% compared to 2.1% among women (p=0.002). Age and household socio-economic status was positively associated with reporting vision problems and assistive device use, respectively. Conclusions: The results from this analysis showed that despite the high reporting of vision problems, only 2.9% reported using assistive devices. This outcome shows that there is a need to prevent vision problems and increase access to assistive devices among older people in the Kassena-Nankana district in Ghana.